Post-Adoption Determinants of Continuance Intention: The Mediating Role of Satisfaction among Indonesian Canva Pro Users - Ima Kumala Safmi; Nurul Komari; Erna Listiana; Ana Fitriana; Ahmadi (Journal of Educational Management Research, 2026)
Cloud-based graphic design platforms have significantly expanded global creative accessibility; however, Canva’s market share in Indonesia has declined by 14.14% to 9.01% despite high digital penetration. This study aims to analyze the post-adoption determinants of continuance intention among Indonesian Canva Pro users by integrating the Expectation Confirmation Model (ECM) and the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2). A quantitative approach was employed through a survey of 230 active Canva Pro subscribers, and the data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that confirmation of expectation, perceived enjoyment, and price saving orientation positively and significantly influence satisfaction. Furthermore, satisfaction, confirmation of expectation, and price saving orientation have direct significant effects on continuance intention, while perceived enjoyment affects continuance intention indirectly through satisfaction. Mediation analysis confirms that satisfaction serves as a significant intervening variable linking cognitive, affective, and economic factors to continuance intention, with price saving orientation emerging as the most dominant determinant. These results imply that sustaining subscription-based digital services in utilitarian contexts requires not only fulfilling user expectations and delivering enjoyable experiences, but more importantly, ensuring strong perceived economic value to strengthen long-term user retention strategies.